Analysis of Casting Defect, Tensile Strength, and Hardness of Al-Si Casting Alloy with Percentage Variation of Clay Binder Bangkalan - Imam Muhtarom; Sunomo Sunomo (Journal of Mechanical Engineering Science and Technology (JMEST), 2018)
Casting is one of method that used in forming the work piece by melting specific metal and pouring into moulding that has been prepared. This study aimed to determine the effect of the use of Bangkalan clay as binder in sand moulding against tensile strength, hardness, and defects in Al-Si casting alloy by using gravity casting method. The method used in this study was experimental method then using descriptive analysis. Descriptive analysis included explanation of the test result of tensile strength, hardness, and the type of surface defect of Al-Si casting. Based on the research result obtained the highest shear strength in wet condition obtained on sand moulding which had the highest tensile strength, that was sand moulding with composition of 12% Bangkalan clay, and 0.5% bentonite. While the highest hardness value of Al-Si casting result obtained on specimen with variation of 12% Bangkalan clay with the value of 131.9 HV. Casting defects that appeared on the surface of all casting product variations. The defects that found were fin defects, pinhole defects, sand loss defects, and surface roughness. Based on the result above, could be concluded that variation of 9% Bangkalan clay and 0.5% bentonite as binder was the best variation.